Efektifitas Progesteron Kering dan Basah Sebagai Perangsang Birahi Ternak Kambing - Rodiah Rodiah; Lalu Ahmad Zaenuri (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2016)
The study aimed to compare the effectiveness of fresh and dry progesterone to stimulate oestrussynchronizationon does. Ten multiparous non pregnant does (first group) were given 75 mg fresh progesterone/head and thesecond group (n = 10 does) was given 75 mg dry progesterone/head. Progesterone sponges were allowed in thevagina for 12 days. Oestrus detection began 24 hours after spongewithdrawal. Oestrus detectionwas conductedevery 6 hours for three consecutive days. The results show that the retention rate was100% in both treatmentgroups. Seventy percent of does belong to the first group and 60% in the second group clearly showed a variety ofpsychologically oestrussymptoms. Score consistency of the mucus of +3 (range between 0 to +4) was shown by70% does in the first grup and 60% in the second group. The duration of oestrusin both goups was notdifferent(18.03 and 18.27 hours, respectively). In sort, wet or dry form of progesterone have no differenteffectiveness as an oestrusinduction on does.